2009
DOI: 10.1074/mcp.m800292-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysregulation of Osteoarthritic Human Articular Chondrocytes Analyzed by Proteomics

Abstract: Mitochondria are involved in many cellular processes; mitochondrial dysfunctions have been associated with apoptosis, aging, and a number of pathological conditions, including osteoarthritis (OA). Mitochondrial proteins are attractive targets for the study of metabolism of the chondrocyte, the unique cell type present in mature cartilage, and its role in tissue degradation. Using a proteomics approach based on two-dimensional DIGE and MALDI-TOF/ TOF mass spectrometric identification of mitochondriaenriched pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
138
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(160 citation statements)
references
References 48 publications
15
138
1
3
Order By: Relevance
“…The hypothesis that this imbalance in signaling may result from the excessive levels of ROS that have been observed in OA cartilage (14,17,18) was supported by the findings that induction of oxidative stress in normal chondrocytes with tBHP reproduced the changes seen in OA cells, whereas treatment of OA cells with anti-oxidants improved the balance of Akt to ERK phosphorylation and improved the anabolic response of the cells to IGF-I.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The hypothesis that this imbalance in signaling may result from the excessive levels of ROS that have been observed in OA cartilage (14,17,18) was supported by the findings that induction of oxidative stress in normal chondrocytes with tBHP reproduced the changes seen in OA cells, whereas treatment of OA cells with anti-oxidants improved the balance of Akt to ERK phosphorylation and improved the anabolic response of the cells to IGF-I.…”
Section: Discussionsupporting
confidence: 56%
“…Oxidative Stress Inhibits IGF-I-mediated IRS-1-Akt Signaling but Activates MEK-ERK-We hypothesized that increased levels of endogenous ROS due to oxidative stress, previously shown to be present in OA cells (11,14,17,18), might act to inhibit IGF-I signaling. To test this, we induced oxidative stress in normal human chondrocytes by incubating cultures for 30 min with 250 M tBHP.…”
Section: Oa Chondrocytes Possess a High Basal Level Of Irs-1 Serine Amentioning
confidence: 99%
“…Reactive oxygen species (ROS), another major determinant of stress, including hydrogen peroxide (H 2 O 2 ), hypochlorite ion, hydroxyl radical and superoxide anion, are involved in normal intracellular transduction and degenerative cellular processes. Increased ROS production is considered to be an important cause of chondrocyte dysfunction and articular cartilage degradation, which leads to the pathogenesis of OA and the aging of cartilage (7)(8)(9)(10). Chondrocytes and cartilage tissues exhibit efficient protective strategies to minimize damage induced by increased ROS production, including H 2 O 2 (7,11).…”
Section: Introductionmentioning
confidence: 99%
“…Its main function is to protect cells and the ECM against the effects of superoxide anion (18). SOD2 has been shown to be down-regulated in OA while SOD3 is decreased in human OA and a mouse model of OA (16,22,23). Recently Scott et al found that all three SOD family members (SOD1, SOD2, and SOD3) were down regulated in diseased cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 recruits monocytes into areas of high inflammation, but the exact signaling pathways still remain unclear. There is evidence to suggest the involvement of prostaglandin E2 (PGE 2 ) in the attraction of monocytes to the site of inflammation (22). It is produced by a variety of cell types either at the time of or after the induction by oxidative stress, inflammation (cytokines) growth factors (17), and tumor necrosis factor alpha (TNF-α), which have been shown to upregulate MCP-1 expression in sensory neurons (23)(24)(25).…”
Section: Role Of Inflammation In Oamentioning
confidence: 99%